2000
DOI: 10.1046/j.1463-1318.2000.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal stenting for relief of colonic obstruction is safe and effective

Abstract: Endoluminal stenting is safe and effective, and cost effective for palliation. We advocate a multicentre randomized prospective trial of best practice emergency surgery vs endoluminal stenting and subsequent elective surgery for large bowel obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
(15 reference statements)
4
17
0
Order By: Relevance
“…One patient died three days after stent insertion from liver failure and widespread metastatic disease. The mean length of stay was four (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] days. This includes one patient with a 17-day stay because of an ongoing, malignant, small-bowel obstruction and another patient with a 19-day stay, which was necessary while waiting for a bed at another institution for convalescence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One patient died three days after stent insertion from liver failure and widespread metastatic disease. The mean length of stay was four (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] days. This includes one patient with a 17-day stay because of an ongoing, malignant, small-bowel obstruction and another patient with a 19-day stay, which was necessary while waiting for a bed at another institution for convalescence.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, there have been many reports of their use as a palliative measure for patients with metastatic disease. [11][12][13][14] A recent review has shown that colorectal stents can be successfully inserted as a palliative procedure with low morbidity and mortality. 15 All publications to date have been case series, single case reports, and reviews.…”
mentioning
confidence: 99%
“…It allowed time for resuscitation, rehydration, and hyperalimentation before surgery and also enabled the patient to avoid stoma formation, which is associated with psychologic stress for its management and financial problems. 6,11 In addition, this procedure may shorten the length of hospital stay and be more cost-effective than surgeries. 6,[16][17][18] In contrast to colorectal cancers, in which the obstructions develop from intraluminal growth, obstructions by metastatic or invasive noncolorectal cancer develop from extrinsic compression.…”
Section: Discussionmentioning
confidence: 99%
“…6,11 In addition, this procedure may shorten the length of hospital stay and be more cost-effective than surgeries. 6,[16][17][18] In contrast to colorectal cancers, in which the obstructions develop from intraluminal growth, obstructions by metastatic or invasive noncolorectal cancer develop from extrinsic compression. Because obstruction and tumor characteristics differ between colorectal cancer and extrinsic tumor-related obstruction, the results of SEMS insertion are expected to be different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation